2022
DOI: 10.1177/07342829221124355
|View full text |Cite
|
Sign up to set email alerts
|

School Psychology Trainees’ Administration and Scoring Errors on the Woodcock-Johnson IV Tests of Achievement

Abstract: Sixty-three Woodcock–Johnson IV Tests of Achievement protocols, administered by 26 school psychology trainees, were examined to determine the frequency of examiner errors. Errors were noted on all protocols and ranged from 8 to 150 per administration. Critical (e.g., start, stop, and calculation) errors were noted on roughly 97% of protocols. Wilcoxon signed-rank tests indicated multiple subtests were more prone to both critical and non-critical (e.g., failure to record answers verbatim, failure to record qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(18 citation statements)
references
References 33 publications
6
7
0
Order By: Relevance
“…We concur with Lockwood et al (2023) that the subjective scoring rules of Writing Samples and Spelling likely contribute to the greater tendency towards critical errors on these subtests. However, like Lockwood and colleagues, we also found that Calculation was more prone to critical errors though it has objective scoring rules.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…We concur with Lockwood et al (2023) that the subjective scoring rules of Writing Samples and Spelling likely contribute to the greater tendency towards critical errors on these subtests. However, like Lockwood and colleagues, we also found that Calculation was more prone to critical errors though it has objective scoring rules.…”
Section: Discussionsupporting
confidence: 88%
“…Like Lockwood and colleagues, we found failures to record verbatim on every protocol (M = 29.98); this provides confirmatory evidence that from early in their training, test administrators are not consistently collecting these data. Similar to Lockwood et al (2023), we found critical errors on nearly every protocol that we examined; both studies also reported a mean of approximately 15 critical errors per protocol. Additionally, both studies found critical errors were most noted on Calculations, Spelling, and Writing Samples, with at least one error found on the majority of protocols.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations